PENERAPAN PEMBELAJARAN METODE GAMIFIKASI DALAM MENINGKATKAN HASIL BELAJAR DI MADRASAH TSANAWIYAH AN-NUR MAKASSAR - A, Rahmi; Bunyamin, Andi; Mustamin; Raehana, Syarifa; Wahab, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of students in the subject of Al-Qur'an Hadith class VIII at Madrasah Tsanawiyah (MTs) An-Nur Makassar. The low learning outcomes are caused by the use of learning methods that are still centered on the teacher so that students are less active, less motivated, and easily feel bored during the learning process. This study aims to determine the application of the gamification method in improving student learning outcomes in the subject of Al-Qur'an Hadith class VIII at MTs An-Nur Makassar. The type of research used is Classroom Action Research (CAR) with a qualitative approach carried out in two cycles. Each cycle consists of the planning stage, action implementation, observation, and reflection. The subjects of the research were the subject teacher of Al-Qur'an Hadith and 30 students of class VIII. Data collection techniques used observation, interviews, documentation, and tests, while the research instruments were in the form of observation sheets and test sheets. Data were analyzed using descriptive analysis by calculating the average value and percentage of student learning completion. The results of the study showed that the application of the gamification method was able to improve students' learning outcomes gradually in each cycle. The average score of students increased from 58.37 in the pre-cycle stage to 71.90 in Cycle I and increased again to 83.93 in Cycle II. The percentage of learning completion also increased from 23.33% in the pre-cycle to 53.33% in Cycle I, then reached 86.67% in Cycle II. In addition to improving learning outcomes, the application of the gamification method was also able to increase students' motivation, activeness, enthusiasm, and participation during the learning process. Thus, the gamification method has proven effective as an alternative learning method to improve students' learning outcomes in the Al-Qur'an Hadith subject for class VIII at MTs An-Nur Makassar.